Analisis Pengaruh Suku Bunga dan Nilai Tukar terhadap Ekspor Total serta Implikasinya terhadap Pertumbuhan Ekonomi di Indonesia (Tahun 2000–2018) - Tulus Widjajanto; Adhi Susano; Ambar Tri Hapsari (Jurnal Pajak dan Analisis Ekonomi Syariah, 2024)
Export activities in the long term can provide foreign exchange income for the country concerned, which will later be used to increase the growth of the country's economy, finance import needs and domestic development. A study by Kusuma and Twin (2012) concluded that exports had a positive and significant effect on national foreign exchange reserves. Exports are therefore one of the important benchmarks to know how much economic growth is in a country. The fluctuating state of exports in Indonesia is a very important thing to pay attention to. Especially in the face of the era of free trade in the Southeast Asia region or the ASEAN Economic Community (AEC), Indonesia is expected to improve its export performance, so that it can compete with other countries. Then it is necessary to know what factors affect the increase and decrease in the value of Indonesia's exports. From the data processing it is known that interest rates and exchange rates together have a significant effect on total exports with α = 0.00390 < from α = 0.05. Parasially, the Bungan tribe had a negative and significant effect on total exports with a significance value of α = 0.0003 < of α = 0.05, and the exchange rate against the US dollar had a positive and significant effect on total exports with a significance value α = 0.0130 < of α = 0.05.